Simultatem Chronicles: The Fear of Imagination and Discrimination and Their Impacts on Preteenagers - Levana Vivian Nurtanto; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2021)
This short story series is a coming-of-age and dystopian series that focuses on the impacts of the fear of imagination and discrimination on preteens and how they cope with it. This fear is shown through a virus named imaginatio virus, a special virus that attacks the main characters to induce imagination. The government made imagination-prevention and discrimination rules to get rid of the virus completely. We explore how the fear of imagination and discrimination affect the four main characters in each story. We apply the theory of social influence, discrimination, and coping mechanisms to show how Dylan, Elias, Bryna, and Corina deal with the effects of discrimination. In our creative work, we show that the four main characters succeed in being confident by focusing on the strength in themselves, finding help in trusted people, and not dwelling in the problem. Keywords: imagination, short stories, discrimination, dystopian, coming-of-age